PENERAPAN STRATEGI PARAFRASE TERARAHUNTUK MENINGKATKAN KEMAMPUAN MENULIS KARANGAN SINGKAT SISWA KELAS IV SD NEGERI 014 SILIKUAN HULUKECAMATAN UKUI - Kemeria Sitorus (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
The problem in this research is the ability to write a short essay of students is low with the average value of 58.25. This is caused by: (a) students are less able to prepare the outline of a well; (B) disadvantaged students elaborated the outline into a complete and coherent essay; (C) less students read essays with correct punctuation; (D) students are less able to respond to the reading essay correctly. Based on this problem researchers want to conduct classroom action research (PTK) with the aim of increasing the ability to write a short essay through the implementation of strategies directed paraphrase. This study was conducted in SD Negeri 014 Silikuan Hulu, Kecamatan Ukui. The subjects were students of class IV with a number of 30 students with details of 15 male students and 15 female students. This study was done 2 cycles, each cycle consists of two meetings with one daily tests. The data collection technique used is the technique of observation activities of teachers and students and the testing techniques brief essay writing skills. The analysis technique used is the analysis of the activity of teachers and students and the results of tests the ability to write a short essay. The results of this study show that implementation paraphrase strategies directed to improve the ability to write concise Elementary School fourth grade students Silikuan Hulu, Kecamatan Ukui. This is confirmed by the data obtained in the research which states that: (a) the activities of teachers has increased in each cycle, meeting first gained 41.66% (category quite perfect), meeting 2 gained 58% (category quite perfect), meetings 3 gained 75% (perfect category), and 4 meeting will acquire 83% (category is perfect); (b) the activity of students has increased at each cycle, meeting one gained 56% (category quite perfect), meeting 2 gained 76% (perfect category), 3 meeting gained 88% (category is perfect), and 4 meeting gained 98% (category is perfect); (c) the results of learning about the ability to write a short essay of students has increased each cycle, the first cycle gained 66.25 and the second cycle obtain 72.75. Increased mastery learning students in the first cycle of 50% and the second cycle by 80%.